2007
DOI: 10.1210/jc.2006-2855
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Serum Adipokines, Insulin Levels, and Bone Density in Girls with Anorexia Nervosa

Abstract: Adiponectin contributes significantly to the variability of bone density, and insulin contributes to bone turnover markers in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
160
4
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 172 publications
(185 citation statements)
references
References 42 publications
15
160
4
6
Order By: Relevance
“…(11) In a small study of 38 girls aged 12 to 18 years, an inverse association was observed between adiponectin and BMD. (19) Taken together, these observations suggest that reduced adiponectin levels also might contribute to the positive association between fat mass and bone mass accrual in childhood. To examine this question further, in this study we investigated the relationship between adiponectin levels as measured in the ALSPAC cohort at age 9.9 years, fat mass, and indices of skeletal development.…”
Section: Introductionmentioning
confidence: 85%
“…(11) In a small study of 38 girls aged 12 to 18 years, an inverse association was observed between adiponectin and BMD. (19) Taken together, these observations suggest that reduced adiponectin levels also might contribute to the positive association between fat mass and bone mass accrual in childhood. To examine this question further, in this study we investigated the relationship between adiponectin levels as measured in the ALSPAC cohort at age 9.9 years, fat mass, and indices of skeletal development.…”
Section: Introductionmentioning
confidence: 85%
“…Girls with AN suffer from a considerable decrease of bone mass [8][9][10]12 [64], girls with AN exhibited a considerable increase of serum OPG. Misra et al [4] suggested that decreased levels of bone resorption markers in girls with AN might indicate a suppressive effect of elevated serum OPG on osteoclast activity and differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…bone-specific alkaline phosphatase, OC, C-terminal cross-linked telopeptide of type I collagen a chain (CTx), N-terminal cross-linked telopeptide of type-I collagen type I collagen a chain (NTx) and/or deoxypyridinoline [9, 10, 21-23, 60, 61] correlating with a decrease in BMD and LP levels [9,10,23]. Several authors have determined OPG concentrations in girls with AN and found that, similar to young females with AN, the girls had elevated serum levels of this cytokine [4,8,21,22,61]. Our earlier investigations revealed that serum sRANKL was increased while the OPG/sRANKL ratio was significantly decreased [21,22,61].…”
Section: Prace Oryginalnementioning
confidence: 99%
See 2 more Smart Citations